Valorization of coffee bean waste: a coffee bean waste derived multifunctional catalyst for photocatalytic hydrogen production and electrocatalytic oxygen reduction reactions - Unni, SreeKuttan M.; George, Leena; Bhange, Siddheshwar N.; Devi, R. Nandini; Kurungot, Sreekumar (RSC Advances, 2016)
Here, we report the valorization of coffee bean waste (CBW) by producing nitrogen doped porous carbon (p-Cof) having both photocatalytic and electrocatalytic properties using a silica templating method. Morphological investigation of p-Cof reveals the presence of assemblies of highly porous flat carbon blocks. p-Cof exhibits a high surface area (1213 m(2) g(-1)) and a wide range of micro-and mesopores with good electrical conductivity. Along with this, the surface of p-Cof displays the presence of graphitic and pyridone-type nitrogen coordinations, which help p-Cof to perform as a multifunctional catalyst as revealed from its catalytic activities towards photocatalytic hydrogen production (PHP) and electrocatalytic oxygen reduction reactions. p-Cof produces 334 mu mol h(-1) g(-1) of hydrogen from water under visible light and 575 mmol h(-1) g(-1) of hydrogen under solar light irradiation with excellent stability. Along with this, p-Cof also displays improved oxygen reduction reaction (ORR) activity in alkaline medium. A better onset potential (0.91 V vs. RHE) and half-wave potential (0.75 V vs. RHE) are displayed by p-Cof compared to the catalyst derived from the simple annealing of CBW without employing the silica template. Along with the better electrochemical activity, p-Cof shows excellent ORR kinetics and electrochemical stability compared to the current state-of-the-art Pt/C.

Vitro and in silico antifungal efficacy of nitrogen- doped carbon nanohorn ( NCNH) against rhizoctonia solani - Dharni, Seema; Sanchita; Unni, SreeKuttan M.; Kurungot, Sreekumar; Samad, Abdul; Sharma, Ashok; Patra, Dharani Dhar (Journal of Biomolecular Structure & Dynamics, 2016)
We have investigated in vitro antifungal efficiency of nitrogen-doped carbon nanohorn (NCNH) against Rhizoctonia solani (R. solani) plant pathogenic fungi. NCNH with size of 50-60nm and concentrations of 10, 50, 100, and 150gmL(-1) were used. The results showed that growth of fungi in the presence of NCNH was significantly (p>.05) inhibited at 150gmL(-1) (85.13 +/-.97) after 72h. The results were validated through computational approaches. Molecular docking analysis of NCNH with endochitinase protein of R. solani was performed to validate the potential of antifungal activity of NCNH. Docking results showed different conformations of interaction of NCNH with endochitinase enzyme. The conformation with least binding energy -13.54kcal/mol was considered further. It is likely that NCNH interacts with the pathogens by mechanically wrapping, which may be one of the major toxicity actions of NCNH against R. solani. The analysis showed that NCNH might interwinds to endochitinase of R. solani leading to the deactivation of the enzyme. To best of our knowledge, this is the first report of antifungal efficacy of NCNH against R. solani and provides useful information about the application of NCNH in resisting crop disease.
Keywords: docking; endochitinase; nitrogen-doped carbon nanohorn; Rhizoctonia solani